Efektifitas Pelaksanaan SUSCATIN di Wilayah Hukum KUA Sekampung dalam Upaya Mencegah Terjadinya Perceraian - Dyah Ayu Vijaya Laksmi (Al Qadhi Journal of Islamic Family Law, 2022)
There were 4 divorce cases experienced by Suscatin participants from the Sekampung District. The causes of divorce include economic factors, domestic violence, and disputes between husband and wife. Based on the interview with the head of the Sekampung KUA, it is known that at the Sekampung KUA Suscatin has been held since 2017. Suscatin's materials include marriage procedures and procedures, legislation in the field of marriage and family, rights and obligations of husband and wife, reproductive health, and family management. Sucatin speakers are delivered by competent experts in their fields. Among them are: from BP4, health workers and academics. The allocation of time used for the implementation of 2 to 3 hours per meeting, and can be extended if there is a request frThere were 4 divorce cases experienced by Suscatin participants from the Sekampung District. The causes of divorce include economic factors, domestic violence, and disputes between husband and wife. Based on the interview with the head of the Sekampung KUA, it is known that at the Sekampung KUA Suscatin has been held since 2017. Suscatin's materials include marriage procedures and procedures, legislation in the field of marriage and family, rights and obligations of husband and wife, reproductive health, and family management. Sucatin speakers are delivered by competent experts in their fields. Among them are: from BP4, health workers and academics. The allocation of time used for the implementation of 2 to 3 hours per meeting, and can be extended if there is a request from Suscatin participants who do not understand the material. . The implementation of Sucatin at the KUA in Sekampung District is still not in accordance with the Islamic Guidance Guidelines number DJ 11/491 of 2009 concerning Sucatin. Both related to materials, methods and resource persons as well as time allocation. This was due to the following findings: 1) Submission of Suscatin's material was only delivered at a glance and lacked depth. 2) The resource persons who delivered the Suscatin material only came from the KUA officers of the Sekampung District. 3) The dominant method used by resource persons in delivering Suscatin material is the lecture method. 4) The allocation of time used in the implementation of Suscatin at the KUA in the Sekampung sub-district was not fully carried out for 24 hours of lessons.om Suscatin participants who do not understand the material. . The implementation of Sucatin at the KUA in Sekampung District is still not in accordance with the Islamic Guidance Guidelines number DJ 11/491 of 2009 concerning Sucatin. Both related to materials, methods and resource persons as well as time allocation. This was due to the following findings: 1) Submission of Suscatin's material was only delivered at a glance and lacked depth. 2) The resource persons who delivered the Suscatin material only came from the KUA officers of the Sekampung District. 3) The dominant method used by resource persons in delivering Suscatin material is the lecture method. 4) The allocation of time used in the implementation of Suscatin at the KUA in the Sekampung sub-district was not fully carried out for 24 hours of lessons.